2017
DOI: 10.1038/bjc.2017.360
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the association between childhood infections and the risk of childhood acute lymphoblastic leukaemia

Abstract: The hypothesis put forward by Greaves and others about an infectious aetiology are neither confirmed nor refuted and the overall evidence remains inadequate for good judgement. The qualitative difference in the subgroup effects require further study, and future research will need to address the challenges in measuring infectious exposures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 87 publications
1
15
0
1
Order By: Relevance
“…These infections were chosen a priori based on the knowledge gained from a systematic review and meta-analysis of common infections in children and the association with the development of childhood acute lymphoblastic leukemia. [ 15 ] We thought these infections would account for the majority of infection-related physician visits. We hierarchically defined each visit to assess whether the visit was for an infection, the corresponding anatomical region, and the specific infectious syndrome.…”
Section: Methodsmentioning
confidence: 99%
“…These infections were chosen a priori based on the knowledge gained from a systematic review and meta-analysis of common infections in children and the association with the development of childhood acute lymphoblastic leukemia. [ 15 ] We thought these infections would account for the majority of infection-related physician visits. We hierarchically defined each visit to assess whether the visit was for an infection, the corresponding anatomical region, and the specific infectious syndrome.…”
Section: Methodsmentioning
confidence: 99%
“…A number of risk factors display significant associations with B-ALL, but not T-ALL, as shown in Fig. 2A-D and Supplementary Table S1, including home paint exposure prior to conception, during pregnancy, and after birth (72), preconception paternal smoking (107), older paternal age (105), prelabor caesarean delivery (84), increasing birth weight (98,108), increasing birth order (98), being breast fed (109), infections during childhood (89,110), and daycare attendance (91,(111)(112)(113).…”
Section: Risk Of All By Immunophenotypementioning
confidence: 99%
“…Some studies indicate that early immune stimulation (e.g., via exposure to infection) may be protective against ALL (Rudant et al 2015;Hwee et al 2018). Using data pooled across 11 studies from the Childhood Leukemia International Consortium, Rudant et al (2015) reported a 23% reduction in risk of ALL among children who attended day care (a proxy for immune stimulation) in the first year of life, with a trend for lower risks at younger start dates.…”
Section: Pediatric Leukemiasmentioning
confidence: 99%
“…Importantly, not all studies support an infectious etiology of ALL. Designing epidemiologic studies to evaluate these hypotheses is challenging-for example, prospective studies are unfeasible due to the rarity of ALL, and factors like recall bias and temporal ambiguity threaten the validity of retrospective studies (Hwee et al 2018).…”
Section: Pediatric Leukemiasmentioning
confidence: 99%